It's Not Only Green that Matters: Understanding Education for Sustainability in Schools - Kuzich, Sonja (Common Ground, 2011)
Sustainability is the buzzword of the decade with so much being touted under this banner that it has become both at once, potent in meaning and, at the same time, meaningless. There are many school leaders and whole school communities that have signed up to be a ‘sustainable school’. With schools ready to embrace the ‘visible’ aspects of sustainability such as the ‘kitchen garden’ and ‘environmental activities’, many fundamental aspects of sustainability are being obscured by ‘green’. This paper challenge us to think deeply about what this enterprise called sustainability is, how teachers have become a central notion in a political and policy agenda, and to consider education in terms of all four pillars of sustainability.